Vaksinasi Kolaborasi Universitas Budi Luhur, Asbisindo, OJK Dan RSUD Pesanggrahan Dalam Mengejar Herd Immunity - Wiwin Windihastuty; Wendi Usino; Goenawan Brotosaputro; Bullion Dragon (Universitas Persada Indonesia YAI, 2023)
During the COVID-19 pandemic, the government issued various policies to tackle the spread of COVID-19. One way to stop the spread of the COVID-19 virus is to vaccinate simultaneously and evenly and provide education about the importance of vaccination. Budi Luhur University takes an active role in carrying out vaccinations to stop the spread of the COVID-19 virus, namely by holding a vaccination center. On one occasion, together with the Association of Indonesian Sharia Banks (ASBISINDO) Jabodetabek and the Financial Services Authority (OJK), Budi Luhur University was supported by the Pesanggrahan Hospital which acted as medical personnel to consult participants before administering the vaccine and the vaccinator provided 1000 doses, preferably for employees and their families. ASBISINDO and the general public. To prevent crowds, registration is done online through a system that has been prepared. Only participants who have registered online are entitled to get the vaccine. The implementing team did not forget to provide education about the importance of vaccines and remind participants that vaccines are not immune to viruses, but vaccines are a form of our efforts to fortify ourselves against virus attacks. The implementation of the vaccination went in an orderly and smooth manner, of the 1000 doses provided, almost all were used. Remaining unused doses because participants who have registered are unable to attend or have registered elsewhere.Keyword : pandemic, vaccination, virus, covid-19, collaboration